2021
DOI: 10.1186/s12903-021-01953-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self-reported oral health among Indonesian adolescents

Abstract: Background and aim With the recognition of health as a subjective state, self-reported oral health has been applied in many epidemiological studies. However, the validity of self-reports may vary across different age groups and socio-cultural backgrounds and by using different tools. This study aimed to assess the validity of self-reported oral health of 15-year-old Indonesian adolescents. Materials and methods This study used data from the Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Due to limited resources, the oral health of the participants was assessed with a self-assessment questionnaire and not by clinical examination. A low accuracy of self-reported questionnaires might be considered [ 45 ], although other authors stated that self-reported oral health is associated with normative indices of oral health [ 46 ]. Further, non-probability sampling methods were used.…”
Section: Discussionmentioning
confidence: 99%
“…Due to limited resources, the oral health of the participants was assessed with a self-assessment questionnaire and not by clinical examination. A low accuracy of self-reported questionnaires might be considered [ 45 ], although other authors stated that self-reported oral health is associated with normative indices of oral health [ 46 ]. Further, non-probability sampling methods were used.…”
Section: Discussionmentioning
confidence: 99%